Practices for network management : in search of collaborative advantage - Vesalainen, Jukka; Valkokari, Katri; Hellström, Magnus, 1975- (Palgrave Macmillan, 2017)
Presenting 17 tools developed through rigorous design science research, this book bridges the relevance gap within network management. In so doing, it proposes a novel system-framework and establishes a path towards a networks-as-practice view on inter-organizational relationships. The systems-framework builds on three institutionalized business practices: Networks-as-coordinated social systems, Networks-as-knowledge-creating platforms, and Networks-as-value-generating entities. Through these tools, Towards Relational Business Practices intends to propose a new managerial praxis and provoke new and improved frameworks and models for network management.
Keywords: Computer industry.; Computer networks.; elektronické knihy; electronic books